Evaluation of the effects of psychological prevention interventions on sport injuries: A meta-analysis - Tranaeus, U.; Ivarsson, A.; Johnson, U. (Science & Sports, 2015)
Objectives: The purpose was to conduct a systematic review of published articles aiming to prevent sports injuries based on psychological interventions and to perform a meta-analysis of the effects in such interventions. News: Different kinds of sport injury prevention strategies have been accomplished such as neuromuscular and warm-up programs. More recently, psychological intervention studies have been completed with the purpose of preventing sports injuries. The most evident predictor is stress. Consequently, most psychological injury prevention interventions incorporate stress management and other psychological skills training. Prospect and projects: The electronic databases and suitable sport psychology journals were searched for published studies. Out of 560 screened articles, 15 were potentially eligible articles. Seven of these articles, with substantial information in the papers or the authors were able to provide us with data after request, were finally included. Conclusion: The result, using a random effect model, showed a total Hedges` g effect size of 0.82 (P < .001), 95% CI (0.55-1.11). The result indicates that psychological injury prevention interventions have a large effect on reducing the number of injuries in sport population.